Unconscious and Distinctive Control of Vocal Pitch and Timbre During Altered Auditory Feedback - Xu, Mingdi; Tachibana, Ryosuke O.; Okanoya, Kazuo; Hagiwara, Hiroko; Hashimoto, Ryu-ichiro; Homae, Fumitaka (Frontiers in Psychology, 2020)
Vocal control plays a critical role in smooth social communication. Speakers constantly monitor auditory feedback (AF) and make adjustments when their voices deviate from their intentions. Previous studies have shown that when certain acoustic features of the AF are artificially altered, speakers compensate for this alteration in the opposite direction. However, little is known about how the vocal control system implements compensations for alterations of different acoustic features, and associates them with subjective consciousness. The present study investigated whether compensations for the fundamental frequency (F0), which corresponds to perceived pitch, and formants, which contribute to perceived timbre, can be performed unconsciously and independently. Forty native Japanese speakers received two types of altered AF during vowel production that involved shifts of either only the formant frequencies (formant modification; Fm) or both the pitch and formant frequencies (pitch + formant modification; PFm). For each type, three levels of shift (slight, medium, and severe) in both directions (increase or decrease) were used. After the experiment, participants were tested for whether they had perceived a change in the F0 and/or formants. The results showed that (i) only formants were compensated for in the Fm condition, while both the F0 and formants were compensated for in the PFm condition; (ii) the F0 compensation exhibited greater precision than the formant compensation in PFm; and (iii) compensation occurred even when participants misperceived or could not explicitly perceive the alteration in AF. These findings indicate that non-experts can compensate for both formant and F0 modifications in the AF during vocal production, even when the modifications are not explicitly or correctly perceived, which provides further evidence for a dissociation between conscious perception and action in vocal control. We propose that such unconscious control of voice production may enhance rapid adaptation to changing speech environments and facilitate mutual communication.